The Association between the First Cry and Clinical Outcomes in CDH Neonates: A Retrospective Study - Yuki Takeuchi; Akiyoshi Nomura; Masaya Yamoto; Satoko Ohfuji; Shunsuke Fujii; Seiji Yoshimoto; Toru Funakoshi; Masato Shinkai; Naoto Urushihara; Akiko Yokoi (MDPI AG, 2023)
Congenital diaphragmatic hernia (CDH) is a life-threatening condition characterized by the herniation of abdominal organs into the thorax, resulting in hypoplastic lungs and pulmonary hypertension. The impact of the first cry, a crucial event for lung transition during birth, on CDH patients remains unclear. This study investigated the impact of the first cry during birth on CDH patient survival, along with other prognosis factors. A multi-institutional retrospective study assessed CDH patient characteristics and survival rates by analyzing factors including the first cry, disease severity, birth weight, Apgar scores, oxygenation index (OI) and surgical closure. Among the CDH patients in the study, a positive first cry was linked to 100% survival, regardless of disease severity (p < 0.001). Notably, the presence of a positive first cry did not significantly affect survival rates in patients with worse prognostic factors, such as low birth weight (<2500 g), high CDH severity, low Apgar scores (1 min ≤ 4), high best OI within 24 h after birth (≥8), or those who underwent patch closure. Furthermore, no significant association was found between the first cry and the use of inhaled nitric oxide (iNO) or extracorporeal membrane oxygenation (ECMO). In conclusion, this study suggests that the first cry may not have a negative impact on the prognosis of CDH patients and could potentially have a positive effect.